1995
DOI: 10.1111/j.1467-971x.1995.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

English in China

Abstract: China has the largest number of English users in the Expanding Circle, but little information is available about the exact number of users and their English proficiency. This paper presents a demographic profile of the users of English in China and the distribution of proficiency among the millions of English users. Also presented in the article is a sociolinguistic profile of the different uses of English in Chinese society. The authors contend that the primary function of English in China is not one of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…Thus, they expected their children to do well in English language learning, as evidenced by the results of the descriptive analyses. These results are consistent with the findings of the studies indicating that Chinese and Brazilian participants showed the desire to learn English as it was prompted by the desire to get a better job or promotion as a means of social ascension (Yong & Campbell, 1995;Friedrich, 2000). The parents in the present study reported that learning English was difficult, so vocabulary was crucial in order to learn the language.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, they expected their children to do well in English language learning, as evidenced by the results of the descriptive analyses. These results are consistent with the findings of the studies indicating that Chinese and Brazilian participants showed the desire to learn English as it was prompted by the desire to get a better job or promotion as a means of social ascension (Yong & Campbell, 1995;Friedrich, 2000). The parents in the present study reported that learning English was difficult, so vocabulary was crucial in order to learn the language.…”
Section: Discussionsupporting
confidence: 82%
“…English is conceived as an important tool for Chinese people to communicate in the global context, and people are equally concerned about the negative effects of the spread of English (Hu, 2009;Niu & Wolff, 2003Zhao & Campbell, 1995). Many hope to promote the Chinese language in order to increase China's influence on the international stage.…”
Section: Policies Concerning the English Languagementioning
confidence: 99%
“…Most of these studies have found that LLS are used significantly differently by various groups of learners. However, to date, there has been little research investigating the successful use of LLS in the different education approaches used to teach language learners, or a comparison of the strategy types adopted by speakers of Mandarin Chinese, the largest ethnic group of English learners in the world (Yong & Campbell, 1995), across different countries and/or areas.…”
Section: Language Learning Strategies (Lls)mentioning
confidence: 99%